EFEK STATUS SOSIAL EKONOMI SISWA DAN DESA-KOTA TERHADAP EFISIENSI SEKOLAH MENENGAH PERTAMA NEGERI (SMPN) DI KOTA PADANG - Muhammad Irfan (Universitas Negeri Padang, 2012)
The issue of efficiency of education is increasingly important in the context of Indonesia’s decentralization implemented to the big bang approach. Padang city has a strong commitment to educational development. This study aimed to measure the efficiency of education in 35 Junior High School in the city of Padang in the academic year 2009/2010. This study also aims to determine the effects of socioeconomic status and economics student urban-rural location. The method used is Data Envelopment Analysis (DEA) and a Different Test. The efficiency rate of school on average 93,31 percent was found. Subsequent findings that the school has a student-classroom ratio smaller have a higher level of efficiency. Schools efficiency characterized also by student-classroom ratio is small anyway. Different test result showed that schools with an average student socioeconomic status have a higher average level of efficiency higher than schools with lower socioeconomic status. School located in the city has an average efficiency level higher than rural schools.